Quantifying Approaches to Discourse for Social Scientists - Scholz, Ronny (Postdisciplinary Studies in Discourse, 2019)
This book provides an overview of a range of quantitative methods, presenting a thorough analytical toolbox which will be of practical use to researchers across the social sciences as they face the challenges raised by new technology-driven language practices. The book is driven by a reflexive mind-set which views quantifying methods as complementary rather than in opposition to qualitative methods, and the chapters analyse a multitude of different intra- and extra-textual context levels essential for the understanding of how meaning is (re-)constructed in society. Uniting contributions from a range of national and disciplinary traditions, the chapters in this volume bring together state-of-the-art research from British, Canadian, French, German and Swiss authors representing the fields of Political Science, Sociology, Linguistics, Computer Science and Statistics. It will be of particular interest to discourse analysts, but also to other scholars working in the digital humanities and with big data of any kind. Ronny Scholz coordinates the ERC-funded DISCONEX project on academic discourses at the University of Warwick, UK. His work focuses on the question of legitimisation of power in political discourses especially in the post-democratic era. He uses lexicometric tools as quantifying heuristic helping to explore new perspectives in various corpora of political discourse.